Physical and morphological characteristics of edible coatings based on pectin and guava by-products applied to guava pieces - Todisco, Katieli Martins [UNESP] (2021)
Edible coatings based on polysaccharides have been applied on pieces of fruits and vegetables before drying because of their potential to improve physical and nutritional characteristics of dehydrated plant foods. In the present study, physical and thermal properties of pectin-based films, with and without the incorporation of by-products obtained from the processing of red guava, were determined. These properties allow one to predict the likely behaviour of these films when used as edible coatings on guava pieces, during and after their dehydration. Thus the structural and morphological characteristics and the physical, thermal and sorption properties of the films and of the fruit pulp were determined, using scanning electronic microscopy (SEM), differential scanning calorimetry (DSC), X-ray diffraction (XRD) and the static gravimetric method to determine the water-sorption curves. The addition of by-products provided crystallinity to the pectin film, attributed to their cellulose content, and hardly altered the water retention capacity of the pectin films. However, the pectin contributed to presenting a slightly higher sorption moisture at equilibrium, as compared to the guava pulp. The glass transition temperatures reported at extremely low moisture contents, both in the pulp and in the films with added by-products, indicated that at intermediate moisture contents, the fruit/film ensemble was in the rubbery state at room temperatures, providing softness to the dehydrated product. The images showed good integration of the edible films with the surface of the guava pieces.